Early referral and planned initiation of dialysis: what impact on quality of life? - Fergus Caskey; Sarah Wordsworth; Thomas Ben; Frank de Charro; Catherine Delcroix; Vladimir Dobronravov; H. van Hamersvelt; Ian R. Henderson; Ε. Κοκολίνα; I.H. Khan; Anne Ludbrook; Merike Luman; et al. (2003)
Early patient referral correlates with improved patient survival on dialysis. We examine whether early referral and a planned first dialysis affect quality of life (QoL).All patients commencing dialysis in nine centres in seven European countries between 1 July 1998 and 31 October 1999 were recruited.early referral=followed by a nephrologist >1 month before first dialysis (<1 month=late referral); planned=early referral and previous serum creatinine >300 micro mol/l and non-urgent first dialysis (early referral and no creatinine >300 micro mol/l or urgent first dialysis=unplanned). QoL was measured at 8 weeks using a visual analogue scale (VAS) and Short Form 36 (SF-36).VAS was significantly higher in early referral patients [mean (SD) 58.4 (20) vs 50.4 (19), P=0.005], particularly if the first dialysis was planned [60.7 (20) vs 54.2 (20), P=0.03]. Planned patients also had higher SF-36 mental summary scores [45.4 (12) vs 39.7 (11), P=0.003], role emotional scores [58.0 (43) vs 30.9 (38), P=0.003], and mental health scores [63.7 (24) vs 54.6 (22), P=0.01] than unplanned patients. Adjusting for centre and other confounding variables showed that having a planned first dialysis had an independent effect on QoL (VAS, and the SF-36's mental summary score, physical functioning, role physical, general health, role emotional and mental health). Early referral had no independent effect on QoL. Socio-economic status had an important positive effect on physical QoL.While the effect of early referral to a nephrologist on QoL appeared centre dependent, a smooth transition onto dialysis was associated with significantly better early QoL, independent of other variables.